The comparison of high school students’ understanding of kinematic materials: Case of question representations - Putri, Hellmy Nur Pratama Annuari; Wulandari, Ratih Niela; Fitriana, Agnes; Kusairi, Sentot (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This present study aimed to compare the understanding on kinematic concepts between public and private high school students in terms of the type of questions representation. Therefore, this quantitative and descriptive study applied survey methods in conducting the research. 190 students of private high school and 199 students of public high school were involved as the research subjects. The main instrument in this study was an isomorphic multiple-choice test which was developed into verbal representations, pictures and graphics. Specifically, this research instrument was adapted from Force Motion Concept Evaluation (FMCE) and High School National Exam which had been validated with a reliability number of 0.74. Another key point, descriptive statistical and inferential independent t-test were used as the data analysis. Consequently, the results showed that there were significant differences in conceptual understanding between private and public high schools’ students. The concept understanding in private high school was lower than in public high school, which was evidenced with the average scores of public high school students by 42,68 and private high school students by 22,93. All in all, high school students are more capable in answering questions over verbal representation instead of understanding the concepts with graphical representations.